Advanced Materials - Soldera, Armand; Soldera, Armand; van de Ven, Theodorus; van de Ven, Theodorus (De Gruyter Textbook, 2020)
Advanced Materials gives an unique insight into the specialized materials that are required to run our modern society. Provided within are the fundamental theories and applications of advanced materials for metals, glasses, polymers, composites, and nanomaterials. This book is ideal for scientists and engineers of materials science, chemistry, physics, and engineering, and students of these disciplines.